Structurally diverse bufadienolides from the skins of Bufo bufo gargarizans and their cytotoxicity - Lingjie Meng; Qian Cao; Xinyi Du; Huijing Lv; Chengjin Li; Xiaoke Zhang; Nian Jiang; Yi Xiao (Scientific Reports)
Abstract Natural products, with their extensive chemical diversity, distinctive biological activities, and vast reservoirs, provide a robust foundation for advancing cancer therapeutics. A comprehensive phytochemical investigation of the skins from Bufo bufo gargarizans afforded two new bufadienolide derivatives identified as bufalactamides A and B (1–2), along with six known compounds: argentinogenin (3), desacetylcinobufagin (4), desacetylcinobufaginol (5), cinobufaginol (6), bufalin (7) and gamabufalin (8). The structural elucidation of these compounds was meticulously carried out by analyses of spectroscopic data (1D and 2D NMR, HR-ESIMS), and comparison with the literature data. Plausible biosynthetic pathways for the new compounds were also discussed. Moreover, the cytotoxicity of the compounds was investigated using various cancer cell lines, including lung cancer (A549), colon cancer (HCT-116), liver cancer (SK-Hep-1), and ovarian cancer (SKOV3). Our research findings indicated that compounds 3, and 6–8 exhibit potent cytotoxic activity (IC50 < 2.5 µM). In contrast, compounds 4 and 5 display moderate cytotoxic activity (IC50 < 50 µM) while compounds 1 and 2 show no cytotoxic activity (IC50 > 100 µM). From this data, we conducted a comprehensive analysis of the structure-activity relationships among these compounds.